High Dose Indomethacin for Patent Ductus Arteriosus Closure Increases Neonatal Morbidity - Waldvogel, Salome; Atkinson, Andrew; Wilbeaux, Mélanie; Nelle, Mathias; Berger, Markus R.; Gerull, Roland (American Journal of Perinatology, 2019)
Objective Symptomatic patent ductus arteriosus (sPDA) is the most common heart abnormality in preterm infants. Optimal duration and dose of medical treatment is still unclear. We assessed undesired effects and closure rate of high-dose indomethacin (HDI) for pharmacological closure of sPDA.Study Design Retrospective single center analysis of 248 preterm infants born between January 2006 and December 2015 with a birth weight <2,000 g and sPDA which was treated with indomethacin. Patients were treated with either standard dose indomethacin (SDI; n = 196) or HDI (n = 52). Undesired effects and PDA closure were compared between patients treated with SDI and HDI.Results In univariate analysis, patients receiving HDI had a significant increase in gastrointestinal hemorrhage (32.7 vs.11.7%, p = 0.001), bronchopulmonary dysplasia (BPD) (77.8 vs. 55.1%, p = 0.003), and retinopathy of prematurity (13.5 vs. 2.6%, p = 0.004). Moreover, HDI patients needed longer mechanical ventilation (2.5 vs. 1.0 days, p = 0.01). Multivariate analyses indicated that necrotizing enterocolitis (17 vs. 7%, p = 0.01) and BPD (79 vs. 55%, p = 0.02) were more frequent in HDI patients. PDA closure rate was 79.0% with HDI versus 65.3% with SDI.Conclusion HDI used for PDA closure is associated with an increase in necrotizing enterocolitis and BPD. Risks of HDI should be balanced against other treatment options.
Keywords: patent ductus arteriosus; preterm; indomethacin; retinopathy of prematurity; bronchopulmonary dysplasia; necrotizing enterocolitis